AB0251 Small intestine enteropathy in patients with rheumatoid arthritis and osteoarthritis. (23rd January 2014) - Bradna, P.; Tacheci, I.; Rejchrt, S.; Soukup, T.; Toms, J.; Bastecka, D.; Bures, J.
Abstract : Background: Involvement of small intestine is demonstrable up to 72% of patients, using non-steroidal antirheumatic drugs (NSAIDs). Quite little is known about influence of principal diagnosis on incidence and severity of enteropathy. Objectives: Aim of our study was to compare small bowel enteropathy in rheumatoid arthritis and osteoarthritis patients. Methods: Capsule endoscopy is currently the leading method for non-invasive diagnostics of small bowel lesions. This method is safe, reproducible, with high diagnostic yield, discriminating extend localization, severity and character of lesions. We examined 37 rheumatoid arthritis (RA) patients and 14 patients, using NSAIDs on a regular basis for osteoarthritis (OA). Group of 13 healthy persons not using NSAIDs served as a control group. We excluded people with comorbidities potentially involving the bowel or leading to a blood loss. We evaluated extend, severity and localizations of lesions. Qualitative data were evaluated by Fisher's exact test, Armitage test or chi2 test, quantitative data were evaluated by Student's T-test or Mann Whitney test in case of nonparametric distribution Results: We demonstrated enteropathy in 67.5% of rheumatoid arthritis patients, moderate or severe lesions in 20% of RA patients. In osteoarthritis group there was 42.9% patients with enteropathy, severe in 7% of them. In control group there was demonstrated only mild changes in 15% people. Moderate or severe lesions were not demonstrating in NSAIDs non-users. Lesions were equally frequent in ileum and jejunum, duodenum was involved rarely. The same distribution was demonstrated also in moderate and severe lesions. Conclusions: Rheumatoid arthritis patients, using non-steroidal antirheumatic drugs have significantly more frequent and more severe lesions of small bowel then osteoarthritis NSAIDs users. Jejunum and ileum were involved with equal frequency and severity, duodenal involvement was rare. Next studies must reply, if differences are caused by genetic predisposition, co medication, or they are caused by direct impact of rheumatoid arthritis. Disclosure of Interest: None Declared